(untitled) (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2014)
In the present age of science and technology, teachers are under stress due to increasing complexities of work and its divergent demands. Organizational climate is the important factor in contributing best work from teachers and students. If organizational climate is good then teachers will freely enjoy their work and can give their best to students. Congenial atmosphere of institution and good relationships can minimize their occupational stress. Teacher who is source of shaping destiny of country, in the form of making educated and well adjustment students in the class rooms, can be a best productive source only if he is getting teaching environment with no occupational stress. The present paper deal with the relationship between organizational climate and occupational stress of teachers.